Implementasi Pembinaan Narapidana Terorisme Di Lembaga Pemasyarakatan Dalam Kerangka Deradikalisasi - Indra Rukmana (Syntax Literate, 2020)
ABSTRAK The study of "Implementation of Terrorist Prisoners Development in Corrections Institutions" aims to describe the implementation of fostering carried out in Penitentiaries against perpetrators of criminal acts of terrorism; as well as identifying what things need to be done to improve the quality of guidance for terrorist prisoners in prison. The method used in this study is a qualitative method. Data collection techniques using literature study and in-depth interviews. The results of the study showed that ineffective guidance for inmates in correctional facilities was caused by the following things: lack of integration in handling the perpetrators of terrorism crimes, inadequate implementation of existing coaching standards, lack of existing facilities and infrastructure, passive prisoners themselves, lack of training for officers prison, as well as the culture of the people who are still relatively difficult to accept former terrorists after they left the Suppliers Institute. Suggestions that can be given include that the government, especially the Directorate General of Corrections and the BNPT (National Agency for Terrorism Prevention) to make a training program and develop a special training model for terrorist prisoners who are systematically comprehensive, humanist, and sustainable. In addition, BNPT and the Directorate General of Corrections need to improve training for correctional officers to improve their understanding of various specific aspects of fostering terrorism inmates.